Tempo, espaço e memória: fronteiras do relato em Cinzas do Norte - Assis, Rosangela Freitas de (2011)
The study of Cinzas do Norte novel written by the manauara Milton Hatoum (2005) is about the reminder report of the Amazon history built by the redesigning of time and space connections. Dissolving the inventive past, correspondent relations between chronotopes and anachronism articule the writing of memory experience to the narrator characters in metafictional labor without marking social and geographic frontiers. In this event, the artistic and epistolary genres have a mediator role in the hybrid speech of the relate between narrators, and characters while sharing the communication among the past memories, felicity appeal, and future dreams of a new Amazon. The demonstration of metafictional construction of Cinzas do Norte relate is announced in a triadic context: in the errant frontiers of the time, space and place, in the bivocal discurse of the letters, and the visual art, and in the physical and human space up dated by the ironic and parodic discurses questioning supports of historical-social chronotope. The reached interpretation expands the history of Amazon by the semantic ambiguity, by the historical critical and the poetic revitalization of ecologic and humanist local language